PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI, DUE PROFESSIONAL CARE, AKUNTANBILITAS, KOMPLEKSITAS AUDIT DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT (Students' Journal of Accounting and Banking, 2015)
This study aims to examine Influence Auditor Experience, Independence, Due Professional Care, Accountability, Complexity Audit and Ethics Audit on the Quality Auditor. Several previous studies on Audit Quality showed different results. Therefore, it is necessary to study in order to verify the theory of Quality Audit. The population in this study were all auditors working in the public accounting firm in the province of Central Java and Yogyakarta. The sampling technique used was purposive sampling, ie sampling based on certain criteria. The criteria for sampling in this study is the auditor who works in the Office of the Public Accounting at least 1 year. This study using multiple linear regression test. The results showed that: Experience the auditor has a positive influence on the quality of auditors. The independence of having a positive effect on audit quality. Due care professionals have a positive effect on audit quality. Accountability has no effect on audit quality. The complexity of the audit no effect on audit quality. Ethics auditors have a positive effect on audit quality.Keywords: Experience Auditor, Independence, Due Professional Care, Accountability, Complexity Audit, Ethics and Quality Audit Auditor